2020
DOI: 10.3174/ajnr.a6621
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Machine Learning to Differentiate Pediatric Posterior Fossa Tumors on Routine MR Imaging

Abstract: BACKGROUND AND PURPOSE: Differentiating the types of pediatric posterior fossa tumors on routine imaging may help in preoperative evaluation and guide surgical resection planning. However, qualitative radiologic MR imaging review has limited performance. This study aimed to compare different machine learning approaches to classify pediatric posterior fossa tumors on routine MR imaging. MATERIALS AND METHODS:This retrospective study included preoperative MR imaging of 288 patients with pediatric posterior fossa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…Several studies have shown the feasibility of PFT classification using conventional machine learning and MRI data. A few studies used histogram textural analysis and visual based features extracted from diffusion and conventional MRI, and patients' clinical features [6,[16][17][18][19][20][21][22][23].…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have shown the feasibility of PFT classification using conventional machine learning and MRI data. A few studies used histogram textural analysis and visual based features extracted from diffusion and conventional MRI, and patients' clinical features [6,[16][17][18][19][20][21][22][23].…”
Section: Related Workmentioning
confidence: 99%
“…To enhance the scalability and interpretability, a template for the searched pipeline can be specified, and a selector of the feature set can be appended as the input preprocessing port for every pipeline to separate the model training data by different small feature sets, thus allowing genetic programming to seek the best performance pipeline [ 59 ]. TPOT has been successfully applied in biomedicine [ 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…In [106], an AutoML model was proposed to do three-way and binary classification of the main types of pediatric posterior fossa tumors based on routine MRI prior to an operation. Here, contrast-enhanced T1-weighted images, T2-weighted images, and ADC maps from histologically confirmed 111 MB, 70 EP, and 107 PA fossa tumor patients are utilized in order to extract radiomics features.…”
Section: ) Ml-based Approaches In Brain Tumor Diagnosismentioning
confidence: 99%